Phase Transition and Liquid Crystalline Organization of Colloidal Graphene Oxide as a Function of pH. (30th March 2017) - Tkacz, Rachel; Abedin, Md Joynul; Sheath, Phillip; Mehta, Shalin B.; Verma, Amitabh; Oldenbourg, Rudolf; Majumder, Mainak
Abstract : This paper discusses the influence of pH on colloidal graphene oxide (GO) liquid crystals. The results indicate that there is a crossing point where suspensions at pH > p K a, the GO sheets have different behavior than suspensions at pH < p K a . This behavior is evidenced by broadening of the biphasic region in the isotropic to nematic phase transition, by observing different shape and internal configurations of the nematic droplets, and in the magnitude of fractionation between large and small sheets in the nematic and isotropic phases. The behavior of GO liquid crystal droplets under the influence of a static magnetic field is studied, and evidence is found in the magnetically induced distortions for the support of our interpretation of the internal configurations of the nematic droplets. This study also demonstrates that magnetic distortions are reversible on a time scale of minutes to hours. This research is based on the LC‐PolScope, a polarized light system, which is found to be a powerful tool for characterization of GO liquid crystals due to its fast and easy image acquisition and analysis. Abstract : Colloidal graphene oxide (GO) suspension reveals pH‐dependent isotropic to nematic phase transition by broadening the biphasic region influenced by size fractionation of GO sheets. A highly organized GO nematic droplet of uniform size with isotropic interior forms in this region. This droplet shows reversible magnetic distortion under static magnetic field.